Multitarget Tacrine Hybrids with Neuroprotective Properties to Confront Alzheimer's Disease - Spilovska, Katarina; Korabecny, Jan; Nepovimova, Eugenie; Dolezal, Rafael; Mezeiova, Eva; Soukup, Ondrej; Kuca, Kamil (Current topics in medicinal chemistry, 2017)
Alzheimer's disease (AD) is a multifactorial neurodegenerative disorder. Several hallmarks such as β-amyloid (Aβ) aggregation underlying amyloid plaque formation, τ-hyperphosphorylation leading to production of neurofibrillary tangles, and decline in the number of cholinergic neurons appear to be fundamental in the pathophysiology of the disease. Other evidence points also to the involvement of oxidative stress, biometal dyshomeostasis, inflammation, and cell cycle regulatory failure. Taking into account such premises, many attractive targets for the development of anti-AD drugs have emerged. Specifically, the multifactorial nature of AD calls for multi-target-directed ligands (MTDLs) which can be beneficial by providing interactions with multiple targets. Tacrine (THA), the first clinically effective acetylcholinesterase inhibitor, was approved for the treatment of mild to moderate AD. Unfortunately, frequent adverse effects including peripheral cholinergic effects and hepatotoxicity limited its therapeutic potential. Based on the numerous biological systems involved in AD progression, this review covers THA-incorporated hybrids possessing a neuroprotective profile. In particular, it focuses on THA hybrids capable of scavenging reactive oxygen species (ROS), and derivatives which reduce the formation of Aβ-plaques either directly by confronting the Aβ1-42 selfaggregation process or indirectly by inhibiting the BACE-1 enzyme or AChE-induced Aβ1-40 aggregation. Particular interest is also addressed to THA hybrids with suppressed hepatotoxicity.
Keywords: takrin; Inhibitors; Multi-target drugs; Alzheimerova nemoc; Alzheimer Disease; Animals; neuroprotektivní látky; lidé; Neuroprotective Agents; Tacrine; Alzheimer disease; Acetylcholinesterase; Tacrine.; Humans; Butyrylcholinesterase; zvířata